Interstices Issue 16: The urban thing CFP - Douglas, Andrew; Hopewell, Hannah (Interstices: Journal of Architecture and Related Arts, 1970)
The Urban Millennium, as the United Nations Population Fund (UNFPA, 2007)1 terms this century’s anticipated mass urbanisation, is well upon us. Yet what is this millennial thing that we enter into or that, more precisely, is settling upon us? The sheer volume of discourses seeking to account for the urban likely point to deeper cultural anxieties about the worth, utility, and even the sense of cities. Worse, the plethora of claims on the evolving value of urban place potentially operate as cover for something far more disconcerting – what Jean-Luc Nancy, recognising a lapse in world-naming and centring (as found in the perenial papal address Urbi et orbi), has referred to as a building “glomicity”, a planetary urbanism without urbanity or civility (2007: 37). For Saskia Sassen, cities contribute to a “savage sorting” subsisting with the hyper-financialisation and reduction of the social and public realms worldwide (2014: 4). As such we might wonder at the sheer brutality (nevermind banality) of the commodification unfolding with the network vectors of the urban phenomenon. Further, if we follow Arjun Appadurai and James Holston (2003), cities – with their sorting out of the trustworthy from the suspicious, the haves from the have-nots and the positing of new economic and cultural elites - are at one level antithetical to national territoriality, and at another, are incubators precisely where the tumult of citizenship is worked out against a backdrop of highly contested, sometimes violently contested, identity claims.Henri Lefebvre (2003), rejecting appeals to ‘the city’ itself as a meaningful measure of post-industrial sociality, has asserted, as early as the 1960s, the irreversable presencing of a global, “urban phenomenon”, one problematically fitting out the world according to the socioeconomic and sociopolitical fields of global capitalism. Such a phenomenon, for Lefebvre, testifies to a plethora of far from synchronous logics – of “things (objects) [,…] of play (or sports)”, of capital etc. – to the point that “there are faults, voids, and lacunae everywhere” (2003: 86). Consequently, any analysis of the operational levels of the urban phenomenon and its object and spatial fields, reveal a remainder irreducable to the logistics attempting to take hold of it. If for Lefebvre something like a “differential space” - of heterogenous aggregation or accumulation (2003: 125) - defines the urban, and one only operates within it as if in a “blind field”, a quest to know the urban phenomenon comes up against a “virtual object” of uncertain ontological basis. If for Lefebvre, in the previous century a metaphilosophy of the urban was demanded (2003: 64-65) , what contra-philosophy might be aposite for this urban millennium? With this in mind, we invite you to contribute your own projects and thoughts on an urban metaphilosophy in the forthcoming issue of Interstices, Journal of Architecture and Related Arts titled “The Urban Thing”.For Bruno Latour (reading Martin Heidegger), the etymology of the word ‘thing’ reveals beneath our now routine association of it with mute objects and brute materiality, a cluster of older associations centred on public assembly and political convening. Taking things themselves to be indicative of complex assemblies, Latour calls for a substitution of a Realpolitik - itself underwritten by a human/nonhuman division - by a Dingpolitik, a new attendance on the articulatory, conjoining agency of things themselves. What might a Dingpolitik of the urban that resists or is richer in intimacy than commodity culture offer? What ontological frameworks might counter older logics of expulsion? Might the new object ontologies centred on the autonomy of things offer renewed vantage - Karen Barad’s “material-discursive practices” (2007: 146), Graham Harman’s (2005) “object orientated philosophy” or Katherine Hayles’ (2013) speculative aesthetics for instance? Are there as yet unrecognised complexities harboured by our culture of ubiquitous things as suggested in Bill Brown’s “thing theory” (2004)? Or might today’s exclusionary logic directed to peoples and biosphere draw on Giorgio Agamben’s (2007) thinking through of the cultic drive underwriting capitalist profanation? Do Tonino Griffero’s (2014) atmospheric “quasi-objects” or Latour’s “phantom public” provide better expositional tools for apprehending the urban phenomenon today? Indeed, what do we get at all by thinking about phenomena and things themselves as ‘urban things’?Please submit full papers for the Interstices 16 journal issue to Dr Susan Hedges (shedges@aut.ac.nz) by 19 June 2015.Interstices accepts both academic and practice-oriented, fully written as well as visual, contributions that engage with the issue theme. For the double blind refereed section of the journal, we welcome submission of 5000 word papers and visual submissions with an accompanying text of approximately 500 words. For the non-refereed section, we welcome papers up to 2500 words and project reports and reviews of up to 1000 words. Visit our website to view the Guidelines for Submissions for details about the reviewing process, copyright issues and formatting: http://interstices.ac.nz/information-for-contributors/guidelines-for-submissions/. We look forward to your contribution!Issue Editors: Andrew Douglas & Hannah HopewellReferences: Agamben, G. (2007). Profanations (J. Fort, Trans.). New York, NY: Zone Books.Appadurai, A. & Holston, J. (2003). Cities and citizenship. In N. Brenner, B. Jessop. M. Jones, G. MacLeod (Eds.), State/space: A reader (pp. 296-308). Malden, MA: Blackwell.Barad, K. (2007). Meeting the universe halfway: Quantum Physics and the entanglement of matter and meaning. Durham, NC & London, England: Duke University Press.Brown, B. (2004). Thing theory. In Brown, B. (Ed.), Things (pp. 1-22). Chicago, Ill & London, England: The University of Chicago Press.Griffero, T. (2014). Atmospheres: Aesthetics of emotional space (S. De Sanctis, Trans.). Farnham, England & Burlington, VT: Ashgate Press.Harman, G. (2005). Guerrilla metaphysics: Phenomenology and the carpentry of things. Peru, IL: Open Court Publishing.Hayles, N. K. (2014). Speculative aesthetics and object orientated inquiry (OOI). Speculations: A journal of speculative realism, 158-179.Latour, B. (1993). We have never been modern (C. Porter, Trans.). Cambridge, MA & London, England: Harvard University Press.Latour, B. (2005). From Realpolitik to Dingpolitik, or how to make things public. In, Making things public – atmospheres of democracy, exhibition catalogue, March-August 2005, ZKM Centre for Art and Media, Karslruhe.Lefebvre, H. (2003). The urban revolution (R. Bononno, Trans.). Minneapolis, MN & London, England: University of Minnesota Press.Nancy, J.-L. (2007). Urbis et Orbi (F. Raffoul & D. Pettigrew, Trans.). In The Creation of the world or Globalization (pp. 31-56). New York, NY: Suny Press.Sassen, S. (2014). Expulsions: Brutality and complexity in the Global Economy. Cambridge, MA & London, England: Harvard University Press.